Micrometeorological Methods for Greenhouse Gas Measurement - Zaman, M.; Kleineidam, K.; Bakken, L.; Berendt, J.; Bracken, C.; Butterbach-Bahl, Klaus; Cai, Z.; Chang, S.X.; Clough, T.; Dawar, K.; Ding, W.X.; Dörsch, P.; et al. (Springer, 2021)
Micrometeorological techniques are useful if greenhouse gas (GHG) emissions from larger areas (i.e. entire fields) should be integrated. The theory and the various techniques such as flux-gradient, aerodynamic, and Bowen ratio as well as Eddy correlation methods are described and discussed. Alternative methods also used are Eddy correlation, mass balance techniques, and tracer-based methods. The analytical techniques with current state-of-the-art approaches as well as the calculation procedures are presented.